Language learning going global: linking teachers and learners via commercial Skype-based CMC. Issue 6 (17th August 2016) - Terhune, N.M.
Abstract: This paper reports on students' use of face-to-face synchronous computer-mediated communication (CMC) for oral language learning. It describes a university English language class designed to prepare students for overseas study in which a Skype-based English conversation school was piloted. The study offers analysis of how students used the CMC language school in a relatively uncontrolled setting using qualitative data collected from a student survey and quantitative data collected over a 12-week trial period. Motivational aspects of using technology and online chat to study English are generally considered to be high but speaking face-to-face online is not for everyone. The speaking project, although new and exciting initially, did not hold most students' attention throughout the project possibly due to few specific tasks and goals. For motivation to be maintained by students, oral CMC projects should be based on an effective pedagogy that includes concrete tasks and specific goals. This finding validates other research where CMC was used in the classroom. The paper concludes with a discussion of reasons for the lack of student enthusiasm toward the project centering on task-based learning, use of social media for schoolwork in addition to motivational and autonomous learning factors.